(untitled) (Research, Society and Development, 2021)
The present study aimed to analyze the dental practices in elderly patients with dementia through a systematic review. through electronic search in the databases PubMed, Scientific Electronic Library Online (Scielo), Web of Science, Virtual Health Library or Virtual Health Library (VHL), Scopus, Google Academic, in the months of September to November 2020. Gray literature was included through the Digital Library of Theses and Dissertations and OpenThesis. The search used the PECOS strategy (P: patient; E; exposure; Comparison; O outcome; S type of study) through the research question: How are dental practices conducted in elderly patients with dementia? Observational studies (cross-sectional, case-control, and cohort) were considered eligible, in which the research participants had a diagnosis of some type of dementia, aged 60 years or older, and that these practices were conducted in primary care or at home. The included articles were independently selected by two reviewers and disagreements were resolved by a third reviewer. The methodological quality of the selected studies was assessed using the Newcastle-Ottawa Scale, which evaluates the risk of bias. The research pointed out that three selected articles report the insertion of dental practices to elderly patients with dementia, two of moderate quality and one of low quality. Thus, we conclude that the results obtained show the need for studies with more rigorous designs, with lower risk of bias, such as controlled and randomized clinical trials, in order to test hypotheses and produce efficient protocols for the development of techniques for dental interventions for the elderly with dementia.